Speech Actions in Inter-Student Interaction in Organizational Activities at the University of Semarang - Rati Riana; Margaretha Maria Shinta Pratiwi (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2022)
This speech act research is a qualitative research with descriptive analysis to describe the form of speech acts in the interaction between students when organizing. Data collection methods in this study include observation, note-taking techniques, recording, and interviews. The form of the data is the speech used by students who are involved in student organizations at the University of Semarang. The speech studied was in the form of politeness in speech acts when carrying out organizational activities. Meanwhile, the data sources are students who take part in student organizations. The findings of the research on the forms of speech acts used by Semarang University students in organizing, namely locutionary, illocutionary, and perlocutionary. The form of locutionary speech acts includes news, questions, and orders. The forms of illocutionary speech acts include assertive, directive, expressive, commissive, and declarative speech acts. As for the forms of perlocutionary speech acts found, namely giving influence, namely directive ordering, pleading, advising, ordering, and demanding.